Responding to Environmental Issues through Adaptive Collaborative Management From Forest Communities to Global Actors - Colfer, Carol; Prabhu, Ravi (Taylor & Francis, 2023)
Focused on forest management and governance, this book examines two decades of experience with Adaptive Collaborative Management (ACM), assessing both its uses and improvements needed to address global environmental issues. The volume argues that the activation and the empowerment of local peoples are critical to addressing current environmental challenges and that this must be enhanced by linking and extending such stewardship to global and national policymakers and actors on a broader scale. This can be achieved by employing ACM's participatory approach, characterized by conscious efforts among stakeholders to communicate, collaborate, negotiate and seek out opportunities to learn collectively about the impacts of their action. The case studies presented here reflect decades of experience working with forest communities in three Indonesian Islands and four African countries. Researchers and practitioners who participated in CIFOR's early ACM work had the rare opportunity to return to their research sites decades later to see what has happened. These authors reflect critically on their own experience and local site conditions to glean insights that guide us in more effectively addressing climate change and other forest-related challenges. They showcase how global and regional actors will have to work more closely with smallholders, Indigenous Peoples and local communities, recognizing the key local roles in forest stewardship. This book will be of great interest to students, scholars and practitioners working in the fields of conservation, forest management, community development, natural resource management and development studies more broadly.